Self- transcendence and its ludic substitutes. A cultural – developmental approach. - Zagórska, Wanda (Studia Psychologica: Theoria et praxis, 2007)
The category of self-transcendence has many different meanings in psychological theory. It is used in reference to changes in the highest stages of development of the human person (an existential-personalistic approach), as also to overcoming oneself in the four hierarchically ordered levels of consciousness (the stance of transcendental-epistemological realism). The paper aims to show that self-transcendence is an inherent human need which is also being satisfied in contemporary times in a substitutive, ludic way. Analogies were drawn, acknowledging the cultural-developmental approach, between the transcending of conditio humana by the man of traditional cultures who participated in the so-called living myth, and the quasi-overcoming oneself of contemporary man participating in a secondary reality created by cultural phenomena and ludic in nature. The common foundation for such distant phenomena is mythos – a specific way of thinking and approaching the surrounding world. The paper analyses the ludic substitutes of transcending oneself in chosen areas of young adults’ ludic activity on the basis of the presented psychological approaches to the category of self-transcendence and its archaic counterparts, as well as the author’s own empirical findings.